Chronic nitrogen deposition alters the structure and function of detrital food webs in a northern hardwood ecosystem. Issue 6 (1st September 2013) - Gan, Huijie; Zak, Donald R.; Hunter, Mark D.
Abstract : During the next century, atmospheric nitrogen (N) deposition is projected to more than double, potentially slowing litter decomposition by altering microbial community composition and function. If the flow of energy though detrital food webs is diminished by the slowing of decay under higher rates of atmospheric N deposition, this agent of global change could also negatively impact the abundance and composition of soil fauna. To test this hypothesis, we studied soil faunal communities in four sugar‐maple‐dominated forests that comprise a long‐term N deposition experiment. To examine whether changes in soil faunal communities could then feed back to influence litter decay, litterbags with 13 C‐enriched aspen litter were placed in the forest floor in one study site. The microbial community within the litterbags was characterized using PLFA analysis. Overall, long‐term experimental N deposition reduced the abundance of microarthropods (ambient vs. experimental N deposition: 7844 vs. 4357 individuals/m 2, respectively; P = 0.004). We attribute this overall decline partly to the reduced energy flow entering the detrital food web, which has been documented in previous work in our system. Although there was no difference in microarthropod species richness between N deposition treatments, there was a shift in community composition within the most abundant group (Oribatida), indicating species‐specific responses to N deposition. Experimental N deposition reduced the number of microarthropods colonizing litterbags by 41% ( P = 0.014). This was associated with a reduction in 13 C mobilization from leaf litter into microbial biomass. Overall, this study demonstrates that chronic N deposition has a detrimental effect on the soil detritus food web, and that the negative effect may feed back to influence litter decay and ecosystem functioning.